Economic Prospect of Belt and Road Initiatives in Nepal - Poudyal, Biranchi (KMC Research Journal, 2019)
This paper attempts to explore global economic prospect of Belt and Road Initiative with special focus on Nepal. The paper begins with the overall account of BRI and examines how connectivity with China would help in prosperity for Nepal. Furthermore, the paper discusses about funding modality as Kerung-Kathmandu railway under BRI and various other dimensions of the construction. The paper concludes with some recommendations regarding immediate requirements for Nepal that should be addressed via BRI.